Application of Repertory in Management of Non Insulin Dependent Diabetes Mellitus. (Type – II) (Advancements in Homeopathic Research, 2022)
The term diabetes mellitus refer to a group of metabolic disorders characterized by chronic hyperglycaemia.The advent of homoeopathy and its holistic concept opened a new era in the world of medicine. The holistic concept of disease takes not only the clinical symptoms of diabetis mellitus into cognizance but also thee biological, social and psychological aspects of man to give the appropriate treatment whereas the holistic concept of cure gives a special meaning to the word cure.
Keywords: Non Insulin Dependent Diabetes Mellitus; Repertory